Pengaruh Model Pembelajaran Kooperatif Tipe Team Games Tournament Berbantuan Peta Konsep Terhadap Hasil Belajar IPA - Putu Hermayanti; Made Sumantri; I Komang Sudarma (Universitas Pendidikan Ganesha, 2018)
This study aims to determine the differences of science learning outcomes between groups of students who were taught by cooperative learning model of Team Games Tournament (TGT) type assisted concept maps and groups of students who were taught by conventional model in V grade II students in Gugus VI Kecamatan Sukasada, Kabupaten Buleleng academic year 2016/2017. The research design used is non equivalent posttest-only control group design. The population in this study is all students of grade V SD GugusV I Sukasada District, Buleleng District. Determination of sample is done by random sampling technique, so that got two classes that is class V SD Negeri 2 Panji Anom amounted to 33 students as experiment class and class V student of SD Negeri 4 Panji Anom amounted 30 student as control class. The instrument of data collection in this research is multiple choice test (objective) with two stages of analysis that is descriptive static analysis and inferential statistical analysis (t-test). The result of this research is t-test, tct = 14,4> ttable = 1,98 (with db 61 and significance level 5%), so H0 is rejected and H1 accepted. Thus, it can be stated that cooperative learning model of Team Games Tournament type (TGT) with concept map has significant effect on science learning outcomes of class V students in Gugus VI Sukasada Sub-district of Buleleng Regency in the Lesson Year 2016/2017.